The global role of the U.S. economy: Linkages, policies and spillovers - M. Ayhan Kose; Csilla Lakatos; Franziska Ohnsorge; Marc Stocker (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
This paper analyzes the role of the United States in the global economy and examines the extent of global spillovers from changes in U.S. growth, monetary and fiscal policies, and uncertainty in its financial markets and economic policies. Developments in the U.S. economy, the world's largest, have effects far beyond its shores. A surge in U.S. growth could provide a significant boost to the global economy. Tightening U.S. financial conditions-whether due to contractionary U.S. monetary policy or other reasons- could reverberate across global financial markets, with adverse effects on some emerging market and developing economies that rely heavily on external financing. In addition, lingering uncertainty about the course of U.S. economic policy could have an appreciably negative effect on global growth prospects. While the United States plays a critical role in the world economy, activity in the rest of the world is also important for the United States.
Keywords: C15; E32; E52; F13; H30; O51; 330; United States; uncertainty; trade; business cycles; global economy